Turning Points-Actual and Alternate Histories : the Reagan Era from the Iran Crisis to Kosovo. - Carlisle, Rodney P. (ABC-CLIO, 2007)
Turning PointsóActual and Alternate Histories: The Reagan Era explores a time which saw the rise of the political conservatism that has dominated U.S. politics in recent years, as well as the end of the Cold War that drove American foreign policy for nearly a half century.||What if Jimmy Carter had successfully navigated the energy shortage and the Iranian hostage crisis? What if the assassination attempt on Reagan had succeed? What if IranñContra had not become a scandal? These are among the specific topics examined in |The Reagan Era, which looks at 11 crucial events and speculates on the ef.